Peran Diklat Dalam Meningkatkan Kompetensi Guru - Wahyuningsih, Yenik; Ma'ruf, Chasan; Kuncoro, Irfan (STAI Publisistik Thawalib Jakarta, 2024)
The research aims to explain and describe the role of training programs (diklat) in enhancing teachers' competencies. The research methodology employed is a qualitative literature review. Data collection involves documentation, and data processing includes reduction, data presentation, and conclusion. The results indicate that pedagogical competence training encompasses teachers' skills in lesson planning, classroom management, and evaluating student learning outcomes, with the goal of enabling teachers to gain a deep understanding of effective teaching strategies. Professional competence training involves teachers' understanding of curriculum development, educational innovation, and profound knowledge of the subjects they teach. Personal competence training for teachers, encompassing emotional intelligence and strong interpersonal skills, can create a conducive learning environment. Meanwhile, social competence training establishes a positive classroom climate and supports the development of students' character.